2005
DOI: 10.1021/jo050651j
|View full text |Cite
|
Sign up to set email alerts
|

Planar and Pyramidal Tetracoordinate Carbon in Organoboron Compounds

Abstract: Using previously proposed C(BH)2(CH)2 (16, 17) and C(CH)2B2 (22) systems with a central planar tetracoordinate carbon (ptC) atom linking two three-membered rings as building blocks, a series of stable structures containing two and three ptC centers within a molecule have been designed and computationally studied with the DFT (B3LYP/6-311+G) method. Inclusion of a carbon atom ligated with pi-accepting and sigma-donating boron centers into at least one aromatic ring is critical for stabilization of a planar stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 65 publications
3
37
0
1
Order By: Relevance
“…Selected equilibrium bond lengths are listed in Table 1. As Table 1 shows, the bond distances of C-ptC, B-ptC and C-B in the gas phase are 1.401, 1.616 and 1.403 Å (B3LYP), as well as 1.407, 1.617 and 1.419 Å (MP2), in agreement with previous theoretical results [18,25]. The smallest vibrational frequency is 193 (B3LYP) and 161 (MP2) cm À1 , corresponding to the twisting of two three-membered rings (BCptC).…”
Section: The Structure and Stability Of C 3 B 2 H 4 With Ptcsupporting
confidence: 90%
See 1 more Smart Citation
“…Selected equilibrium bond lengths are listed in Table 1. As Table 1 shows, the bond distances of C-ptC, B-ptC and C-B in the gas phase are 1.401, 1.616 and 1.403 Å (B3LYP), as well as 1.407, 1.617 and 1.419 Å (MP2), in agreement with previous theoretical results [18,25]. The smallest vibrational frequency is 193 (B3LYP) and 161 (MP2) cm À1 , corresponding to the twisting of two three-membered rings (BCptC).…”
Section: The Structure and Stability Of C 3 B 2 H 4 With Ptcsupporting
confidence: 90%
“…Similarly, the delocalized ptCcontaining molecules composed of C, B, H atoms were also extensively studied [14][15][16][17][18][19][20][21][22][23][24][25][26]. The smallest organic molecule C 3 B 2 H 4 with ptC, proposed by Minyaev et al [18], can be served as a basic block to build an extended system such as the stable beltlike compounds (C 3 B 2 ) n H 4 (n = 2-6) and tubular compounds (C 3 B 2 ) n [25,31]. The structural skeleton of C 3 B 2 H 4 is similar to that of C 5 2À [2], and its most stable planar conformation with ptC was predicted to have a large HOMO-LUMO gap of 5.73 eV [25].…”
Section: Introductionmentioning
confidence: 99%
“…[137] Similar configurations have been predicted in M@Au 6 (M = Sc, Ti,V ,Cr, Mn, Fe,Co, and Ni)clusters by Luo and co-workers in 2009. [138] Furthermore,p lanar heptacoordinated copper was computationally predicted in the Cu 7 Sc (D 7h )cluster (56)byNguyen and co-workers [139] in 2008 ( Figure 56).…”
Section: Phosphorus and Arsenicmentioning
confidence: 97%
“…Later Pancharatna et al have elegantly extended the systems reported by Merino et al to show that the preference for the ptC will be prevailed even in extended systems 18. This is followed by excellent design of planar tetracoordinate hydrocarbons by the Perez et al12 Esteves et al19 and Minyaev et al20 All these studies have one common objective that the central carbon is engaged in a strong π‐delocalization network and thus impart aromatic stabilization to the system. When the aromatic stabilization of the extended π‐network involving carbon with the tetracoordination overtakes the traditional tetrahedral arrangement, the molecules begin to display the unique preference for the planar geometry.…”
Section: Introductionmentioning
confidence: 97%